The effect of crosslinker on mechanical and morphological properties of tropical wood material composites - Islam, Md. Saiful; Hamdan, Sinin; Rahman, Md. Rezaur; Jusoh, Ismail; Ahmed, Abu Saleh; Idrus, Mun'aim (Elsevier, 2011)
In this study, wood polymer composites (WPCs) based on five kinds of selected tropical wood species, namely Jelutong (Dyera costulata), Terbulan (Endospermum diadenum), Batai (Paraserianthes moluccana), Rubber (Hevea brasiliensis), and Pulai (Alstonia pneumatophora), were impregnated with methyl methacrylate (MMA) and hexamethylene diisocyanate (HMDIC) monomers mixture in the ratio of 1:1 for composite manufacturing. All these tropical wood reacted with hexamethylene diisocyanate and crosslinked with MMA which enhanced the hydrophobic (restrained water) nature of wood. The vacuum-pressure method was used to impregnate the samples with monomer mixture. The monomer mixture loading achievable was found to be dependent on the properties of wood species. Low loading was observed for the high density wood species. Mechanical strength of fabricated wood polymer composites (WPCs) in term of modulus of elasticity (MOE) and modulus of rupture (MOR) were found to be significantly improved. The wood–polymer interaction was confirmed by Fourier transform infrared (FTIR) spectroscopy. Morphological properties of raw wood and WPC samples were evaluated by scanning electron microscopy (SEM) and XRD analysis and an improvement in morphological properties was also observed for WPC.